Peningkatan Kapasitas UMKM Kampung Sedekah Melalui Penerapan Strategi Pemasaran Digital - Rahmawati, Dwi; Pertiwi, Husna Putri; Destiana, Destiana; Andini, Laras Ayu (Abdimas Mandalika, 2026)
Abstract:  Kampung Sedekah Indonesia is a philanthropic organization in Ciracas, East Jakarta, that focuses on empowering MSME communities. The main challenge faced by partners is the lack of marketing strategy assistance to increase competitiveness. This community service program aims to assist MSMEs in designing and implementing innovative and sustainable marketing strategies. The program implementation uses a participatory method that includes four stages: needs analysis, modern marketing training, practical creative marketing assistance, and implementation evaluation. Pre-test results showed that although participants had sufficient basic knowledge, the main obstacles faced were capital and marketing strategies. After the intervention, post-test results showed a significant increase in participants' knowledge and commitment. Key findings noted that 100% of participants committed to separating personal and business finances. In terms of digital marketing, participants demonstrated high readiness, with a preference for Instagram/Facebook platforms for general promotions and TikTok for video content. The program successfully improved participants' digital literacy and practical skills, which is expected to strengthen brand awareness and expand the market reach of Kampung Sedekah MSMEs independently and sustainably.Abstrak: Kampung Sedekah Indonesia merupakan organisasi filantropi di Ciracas, Jakarta Timur, yang fokus pada pemberdayaan komunitas UMKM. Tantangan utama yang dihadapi mitra adalah minimnya pendampingan strategi pemasaran untuk meningkatkan daya saing. Program pengabdian masyarakat ini bertujuan mendampingi UMKM dalam merancang dan mengimplementasikan strategi pemasaran yang inovatif serta berkelanjutan. Pelaksanaan program menggunakan metode partisipatif yang meliputi empat tahapan: analisis kebutuhan, pelatihan pemasaran modern, pendampingan praktis pemasaran kreatif, dan evaluasi implementasi. Hasil pra-test menunjukkan bahwa meskipun peserta memiliki pengetahuan dasar yang cukup, hambatan utama yang dihadapi adalah permodalan dan strategi pemasaran. Setelah intervensi, hasil post-test menunjukkan peningkatan signifikan pada pengetahuan dan komitmen peserta. Temuan kunci mencatat bahwa 100% peserta berkomitmen untuk melakukan pemisahan keuangan pribadi dan usaha. Dalam aspek pemasaran digital, peserta menunjukkan kesiapan tinggi dengan preferensi platform Instagram/Facebook untuk promosi umum dan TikTok untuk konten video. Program ini berhasil meningkatkan literasi digital dan keterampilan praktis peserta, yang diharapkan dapat memperkuat brand awareness serta memperluas jangkauan pasar UMKM Kampung Sedekah secara mandiri dan berkelanjutan.